Bernstein functions : theory and applications - Schilling, René L.; Song, Renming, 1963-; Vondraček, Zoran, 1959- (De Gruyter studies in mathematics, 2012)
This secondrevised andextendededition of the self-contained and unified approach to Bernstein functions and their subclassesbrings together old and establishs new connections. Applications of Bernstein functions in different fields of mathematics (such as probability theory, potential theory, operator theory, integral equations, functional calculi, and complex analysis) are given, with special attention to interpretations in probability theory. An extensive list of complete Bernstein functions with their representations is provided.